What Are The Returns To Regional Mobility? Evidence From Mass Layoffs - Sebastian Findeisen; Wolfgang Dauth; Attila Lindner (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2015)
This paper estimates the effects of regional mobility on individual employment prospects and wages, exploiting rich German social security data spanning over 30 years. Our focus is on unemployed workers with strong labor force attachment who search for employment after being exposed to a mass layoff. By that we concentrate on a group of individuals who are plausibly searching for employment for exogenous reasons. Comparing individuals who stay in the local labor market to movers, we find that employment rates are around 15 percentage points higher for movers three years after the layoff. Large differences in employment rates persist even 10 years after the layoff. In contrast, there are no effects of regional mobility on wages conditional on finding employment.
Keywords: J61; J63; R23; 330